Expression signatures of crucial genes involved during compatible and incompatible interaction in rubber (Hevea brasiliensis) to Phytophthora meadii - Roy, C.B.; Aswathy, C.S. (PLACROSYM XXV: Building Smart & Resilient Farming and Systems Approaches for Prosperity in Plantation Crops Sector, 12-14 December 2023, ICAR-Indian Institute of Oil Palm Research, Pedavegi, Eluru, Andhra Pradesh, p. 136.)
Phytophthora meadii causes abnormal leaf fall disease affecting yield of natural rubber. One of the most difficult and intriguing aspects in the study of biology is to understand the significant events in the interaction between host and pathogen. Phytophthora tolerant (FX 516) and susceptible (RRIM 600) rubber clones were challenge inoculated with P. meadii. RNA sequencing was performed on Illumina Next Generation Sequencing platform and transcriptome data was analyzed. A progression in the number of DEGs was observed in the tolerant clone as compared to the susceptible clone, suggesting an active involvement of transcriptional activity in the tolerant clone. PAMP Triggered Immunity (PTI) functions as the first line of defense response which involve the recognition of pathogen associated molecular patterns (PAMPs) by host cell surface localized pattern-recognition receptors (PRRs) to activate plant immunity. Flagellin Sensing 2 (FLS2) and Chitin Elicitor Receptor Kinase 1(CERK1), which are involved in the pathogen induced signal perception process, are two well documented Pattern Recognition Receptors (PRRs) located upstream of PTI. Down regulation of FLS2 in both clones indicated that FLS2 may be recognized by the effectors secreted by the pathogen in all phases of infection, thereby preventing pathogen invasion. CERK1 might also act as the PRR as CERK1 is required not only for chitin signaling and fungal resistance, but also it plays an essential role in restricting microbial growth on plants. Ourdata clearly showed that in tolerant clone CDPK and Calmodulin (CaM) genes were upregulated, indicating that Ca2+ plays crucial roles in signal transduction during early phase of infection in tolerant clone. However, in the susceptible clone a weak signal transduction was observed in the initial phase and there was no upregulation of CDPK and CaM genes. In both the clones expression of Pto interacting 5(PTI5) which are transcription factors that regulate Pathogenesis Related-1 genes (PR-1) and possessing anti-fungal role was observed, suggesting a difference in early signal perception in both clones. It was observed that most of the R genes were found to be down regulated upon infection in both clones. A non-traditional R gene called RPS2, was found highly suppressed and was slightly induced at mid phase as well as during susceptible interaction. The role of RPS2 gene product in defense signal transduction pathway suggests their involvement in nucleotide triphosphate binding and protein-protein interaction encompassing reception of an elicitor produced by avirulent pathogen. Our study speculates that resistance could be the result of recessive R gene rather than dominant R gene mediated resistance. Therefore, further studies related to susceptibility genes and resistance genes involved during Hevea-Phytophthora interaction and validation of the findings through quantification and real time PCR assays is in progress. Key words: Rubber, Crucial genes, Phytophthora Meadii, Transcriptome
Keywords: Crucial genes; Phytophthora meadii; Transcriptome